Carbon Stock Estimation in the South Coastal Rehabilitation Area of Java Island - Budiadi Budiadi (Jurnal Ilmu Kehutanan)
Carbon conservation is one of important actions for coastal rehabilitation, in particular in the south coast of Java Island with its unique characteristics of strong tide, high salinity and diverse substrates. The research aimed to estimate carbon stocks from various carbon pools in the coast rehabilitation area, including wetland sites (14-year-old mangroves of Avicennia/AV, Rhizophora/RH and mix mangrove/MX, mudflat-sediment/SD, grassland/GR) and dry-sandy site of 18-year-old Casuarina equisetifolia/CS. Three to nine plots were established for observing and measuring vegetation, as well as taking soil sample at 0-20 cm, 20-40 cm, 40-60 cm depths. Tree biomass were estimated by converting treestem diameter using allometric equation. The tree biomass were converted into tree carbon using carbon density of 0.464 for aboveground (AGC), and 0.39 for below-ground (BGC), and to estimate total biomass carbon (TBC). Soil organic carbon (SOC) was analyzed separately, and combined with biomass carbon to estimate total carbon stock in the ecosystems. High variation of tree growth and density were found, especially in mangrove stands, with a low level of natural regeneration. No significant difference of carbon stock in biomass between mangroves and Casuarina was observed. Average TBC in mangroves (46.08 Mg C/ha) was slightly lower than in CS (51.50 Mg C/ha). In below ground (up to 60 cm depth), wetland sites (AV, RH, MX, SD and GR) significantly stored more SOC than dry land (CS). Soil depth significantly affected SOC, but in wetland sites deeper soil contained more carbon than upper, while an opposite trend was observed in CS. Estimated total carbon stock in the coast was 248.52 (±87.21) Mg C/ha, with the lowest in CS (94.46 Mg C/ha) and highest in MX (324.77 Mg C/ha). Rehabilitation activities in the coast possibly improve carbon stock in the ecosystems due to tree biomass, compared to open sites of SD and GR. In the wetland or mangroves, most of carbon was observed as SOC, and less in the dry-land site. The different characteristics of carbon storage in the south coast need different conservation techniques, but both sites need intensive rehabilitation work and artificial regeneration.